Vocational self-efficacy as a moderator on the relationship between perceived social support and students’ interest in TVET programmes in Pakistan - Azeem, Nazia; Muhd Khaizer, Omar; Abdullah, Mat Rashid; Abdullah, Arnida (Universiti Pertanian Malaysia Press, 2022)
Studies have shown that the behaviour of family, friends and significant others shapes young people’s self-belief and interest in Technical and Vocational Education and Training (TVET) programmes. However, limited research has documented how vocational self-efficacy can significantly impact the relationship between perceived social support and students’ interest in Pakistani TVET programmes. Thus, this study utilised quantitative research to examine the role of vocational self-efficacy as a moderator in the relationship between perceived social support and students’ interest in TVET programmes. A total of 386 secondary school students filled out three questionnaires: vocational self-efficacy, perceived social support, and interest in the TVET programmes scale using Social Cognitive Career theory as a theoretical framework. The data were analysed using Structural Equation Modelling (SEM) and statistical analysis using Statistical Package for the Social Sciences (SPSS). The correlation analysis revealed that perceived social support and students’ interest in the TVET programmes were negatively correlated, and vocational self-efficacy was not a moderator. This study benefits the authorities, policymakers, and researchers in supporting TVET programmes in Pakistan.